Genetic testing in children and adolescents with intellectual disability. Issue 6 (November 2018) - Bass, Nick; Skuse, David
Abstract : Purpose of review: Investigation for genetic causes of intellectual disability has advanced rapidly in recent years. We review the assessment of copy number variants (CNVs) and the use of next-generation sequencing based assays to identify single nucleotide variation in intellectual disability. We discuss the diagnostic yields that can be expected with the different assays. There is high co-morbidity of intellectual disability and psychiatric disorders. We review the relationship between variants which are pathogenic for intellectual disability and the risk of child and adolescent onset psychiatric disorders. Recent findings: The diagnostic yields from genome wide CNV analysis and whole exome sequence analysis are high – in the region of 15 and 40%, respectively – but vary according to exact referral criteria. Many variants pathogenic for intellectual disability, notably certain recurrent CNVs, have emerged as strong risk factors for other neurodevelopmental disorders such as autism spectrum disorders, attention deficit hyperactivity disorder, and schizophrenia. Summary: It is now conceivable that etiological variants could be identified in the majority of children presenting with intellectual disability using next-generation sequencing based assays. However, challenges remain in assessment of the pathogenicity of variants, reporting of incidental findings in children and determination of prognosis, particularly in relation to psychiatric disorders.